2020
DOI: 10.1042/bsr20201346
|View full text |Cite
|
Sign up to set email alerts
|

Net platelet clot strength of thromboelastography platelet mapping assay for the identification of high on-treatment platelet reactivity in post-PCI patients

Abstract: High on treatment platelet reactivity (HTPR) leads to more prevalence of thrombotic event in patients undergoing percutaneous coronary interventions (PCI). Dual antiplatelet therapy with aspirin in addition to one P2Y12 inhibitor is commonly administrated to reduce HTPR. However, “one size fits all” antiplatelet strategy is widely implemented due to lacking benefits with tailored strategy. One reason for the failure of tailored treatment might be less specificity of the current indicators for HTPR. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 37 publications
0
9
0
Order By: Relevance
“…In agreement with previous studies [ 22 , 23 ], our study suggests that MA was significantly associated with CHD. MA represented the maximal clot strength and revealed the reactivity of platelets, which is critical in the generation of thrombus [ 24 ]. Application of proper antiplatelet medication and adjustment of MA value within a normal range might reduce the risk of CHD in people with hypercoagulability.…”
Section: Discussionmentioning
confidence: 99%
“…In agreement with previous studies [ 22 , 23 ], our study suggests that MA was significantly associated with CHD. MA represented the maximal clot strength and revealed the reactivity of platelets, which is critical in the generation of thrombus [ 24 ]. Application of proper antiplatelet medication and adjustment of MA value within a normal range might reduce the risk of CHD in people with hypercoagulability.…”
Section: Discussionmentioning
confidence: 99%
“…The MA demonstrates the clot strength which can test the effectiveness of P2Y 12 inhibitors and aspirin by platelet activation with ADP. A study found that an MA of > 47 mm was a strong predictor of platelet resistance and adverse events after coronary stenting [6] .…”
Section: Discussionmentioning
confidence: 99%
“…Several studies were identified that compared the use of thromboelastography vs. LTA to monitor platelet function in patients with ACS treated with PCI [8,[25][26][27][28][29][30][31], with fewer studies identified comparing thromboelastography vs. VerifyNow ® [26,32]. A list of parameters and their associated assays discussed herein is, described in Table 2.…”
Section: Clinical Validation Of Thromboelastography With Plateletmapp...mentioning
confidence: 99%
“…The current gold standard for determining platelet reactivity, LTA, is time-consuming and requires lengthy laboratory-based sample manipulation and specialist expertise as well as large sample volumes [7,8]. Thromboelastography, VerifyNow, and Multiplate, described elsewhere [6], can be performed by non-technical staff outside the laboratory to provide rapid readouts at the patient bedside [6,9,10].…”
Section: Introductionmentioning
confidence: 99%